2016
DOI: 10.1016/j.ijcard.2016.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the Lotus Valve System for treatment of patients with severe aortic valve stenosis and intermediate surgical risk: Results from the Nordic Lotus-TAVR registry

Abstract: The present study demonstrates the efficacy and safety of the repositionable, retrievable Lotus Valve System in intermediate risk patients with AS. The VARC-defined device success rate was 97.4% with a 30-day patient safety and clinical efficacy rate of more than 90%. Less than moderate aortic regurgitation was obtained in 99.4% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…ViV‐TAVI was associated with lower rates of PPM implantation. Newer generation devices showed improved outcomes over first generation devices in TAVI . Future studies carried out using newer generation transcatheter heart valve devices are needed.…”
Section: Resultsmentioning
confidence: 99%
“…ViV‐TAVI was associated with lower rates of PPM implantation. Newer generation devices showed improved outcomes over first generation devices in TAVI . Future studies carried out using newer generation transcatheter heart valve devices are needed.…”
Section: Resultsmentioning
confidence: 99%
“…6 registries with 4,607 patients (36.61%) used “Balloon-expandable SAPIEN Prosthesis” of Edwards Lifesciences (Irvine, California)[ 16 21 ], and one registry with 1,316 patients (10.46%) used “Self-expandable CoreValve Prosthesis” from Medtronic CoreValve (Minneapolis, Minnesota)[ 22 ], 10 registries with total 6,406 patients used both prostheses of SAPIEN Edwards and Medtronic CoreValve [ 23 31 ]. In addition, one registry with 154 patients used Lotus Valve System (Boston Scientific, MA) [ 32 ]; and one registry with 100 patients used a nonmetallic design TAVI system-Direct Flow Medical (DFM) TAVI system [ 33 ]. Transfemoral (TF) and transapical (TA) are two commonly used access routes in TAVI [ 34 ].…”
Section: 1 Bibliographic Research Resultsmentioning
confidence: 99%
“…11 studies reported early safety rate, but it ranged from 10% to 92.2% [ 15 , 19 , 20 , 23 26 , 29 , 31 33 ]. Only three registries reported clinical efficacy [ 19 , 20 , 32 ]. There is no registry reported time-related valve safety.…”
Section: 1 Bibliographic Research Resultsmentioning
confidence: 99%
“…The valve is deployed via controlled mechanical expansion, which allows for precise positioning. The safety and efficacy of the Lotus valve have been demonstrated in patients with severe AS at high or intermediate surgical risk in the Western world [11][12][13][14][15]. However, data about the use of the Lotus valve for Chinese patients are still lacking.…”
Section: Transcatheter Aortic Valve Replacement In Atypical Valve Anamentioning
confidence: 99%